Seawater carbonate chemistry and juvenile development of a coral reef fish - Cane, Jasmine S; Yasutake, Yogi C; McMahon, Shannon J; Hoey, Andrew S; Donelson, Jennifer M (PANGAEA, 2025)
Here, we investigated how projected ocean warming (+1.5°C) during grandparental (F1) and parental (F2) generations of the spiny chromis damselfish (Acanthochromis polyacanthus), influences the sensitivity of F3 juveniles to ocean warming (present-day vs +1.5°C) and/or elevated CO2 (490 μatm vs 825 μatm). After 16 weeks of exposure, aerobic physiology (resting oxygen consumption, maximum oxygen consumption, and absolute aerobic scope), behaviour (boldness and activity), and growth (length and physical condition) were measured in F3 juveniles and the relationships between these performance traits was explored. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from James Cook University (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-10.
Keywords: Acanthochromis polyacanthus; Animalia; Behaviour; Chordata; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Growth/Morphology; Laboratory experiment; Nekton; Pelagos; Respiration; Single species; South Pacific; Temperature; Tropical